A thematic literature review of innovative strategies to prepare nursing students for aged-care. (April 2020) - McAllister, M.; Ryan, C.; Dodd, L.; Goldenberg, M.; Brien, D.L.
Abstract: Background: The exponential rise in people living longer but requiring residential care is adding pressure to already overstretched aged care nurses. Consequently, a person-centred care culture in residential care remains aspirational, rather than a reality. For nursing students in Australia and elsewhere, clinical placements in aged care facilities are under-utilised due to negative perceptions about the likelihood for learning. Creative strategies to engage students to safely challenge ageist thinking and to inspire enthusiasm for learning in this context are needed. Objectives: The purpose of this thematic review of the literature is to better understand challenges related to learning in aged care settings and identify innovative strategies to enhance nursing student learning experiences in residential aged care placements. Review methods: A literature review was undertaken in 2019 using CINAHL, PUBMED, Elsevier, Medline, ProQuest and Google Scholar. The search was limited to papers that were peer reviewed, in English, and published between 2001 and the date of review (mid-2019) in order to situate the review in the new millennium. Results: 47 articles and books were included in the review that introduce solutions and innovative strategies that could be used to improve students' attitudes to learning in aged care and from older people. The literature review was categorized into three main themes, including: barriers to working with older people; the need for pedagogical change to foster empathy; and innovative strategies to address barriers. Conclusion: These themes are useful to consider in designing engaging learning and teaching for nursing students to be effective in working in aged care.